Prescriptive Signs of an 18th Century English-Language Scientific Medical Text - L. V. Yagenich (Научный диалог)
The article is devoted to the problem of studying a written scientific English text in medicine. Attention is paid to the features of its formation as a result of long historical development. The question of the patterns of presentation of prescriptive information in the medical text of the XVIII century, which is considered the final stage of the nationalization of the language of science, is revealed. The author determines that a medical text possessing signs of expressing prescriptiveness functions as informing, regulating and influencing the addressee with the aim of expressing the meanings of duty, recommendation, permission and prohibition. The article contains a definition of prescription in relation to a medical text. The description of the ways of expressing prescriptions by means of linguistic units is presented: verbs used in the passive voice, nouns, adjectives and participles. It is shown that such texts are intended to induce the recipient to accurately follow the instructions of the doctor and to prevent the possibility of double interpretation. The main prescriptions of the medical written English-language scientific text of the XVIII century, used by doctors in relation to the recipients, are identified as having a character that is not compulsory, but politely recommended.